Tanggung Jawab Kaum Awam Dalam Mengaktualisasikan Imannya Menurut Dokumen Apostolicam Actuositatem (AA) - Mawarni Gea (Jurnal Magistra, 2024)
The Church is a community of all God's people, namely all believers who have received baptism in the name of the Father, Son and Holy Spirit and have been united with God the Father through the person of Jesus Christ. As believers, we are called and sent to continue the work of Jesus Christ in the world. This call and mission came from Jesus Christ when He sent His disciples to preach the Gospel throughout the world. “Go therefore and make disciples of all nations, baptizing them in the name of the Father and of the Son and of the Holy Spirit, and teaching them to observe everything that I have commanded you. And know that I am with you always until the end of time (Matt. 28:19-20).” In continuing Her work, the Church hopes that all of God's people will take part. The Second Vatican Council (1962-1965), produced sixteen documents and one of them was the Decree on the Apostolate of the Laity (Apostolicam Actuositatem). In the Lay Apostolate Decree, lay people are called to apostolate. Lay apostolate is a form of involvement of lay people to take part in the Tritasks of Christ, namely as Priest, Prophet and King. Lay people have duties and responsibilities in actualizing their faith through the work and tasks they carry out every day. The faith lived must be expressed and practiced. In actualizing faith, lay people can carry it out through various areas of life, including: in the Church, family, social environment and politics, both nationally and internationally. The involvement of lay people in various areas of life, the Church hopes that their presence will be salt and light for the world. The laity always strive to fight for the common welfare with the spirit of the Gospel. So that with its presence, the Kingdom of God becomes more real in the world and becomes a blessing for many people and becomes the glory of God's name. In this way, the world increasingly knows, accepts and acknowledges Jesus Christ as the only way to the Father because He is the only goal of life.